2021
DOI: 10.1101/2021.05.26.445863
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large protein complex interfaces have evolved to promote cotranslational assembly

Abstract: Assembly pathways of protein complexes should be precise and efficient to minimise misfolding and unwanted interactions with other proteins in the cell. One way to achieve this is by seeding complex assembly during translation via nascent chain engagement. Here, we considered the possibility that the propensity of subunits to cotranslationally assemble is ingrained within the interface hierarchy of protein complexes. Using a combination of proteome-specific structure data and assembly-onset positions determine… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 110 publications
(228 reference statements)
0
7
0
Order By: Relevance
“…We have previously shown that cotranslationally assembling members of the different symmetry groups tend to have larger interfaces (Badonyi and Marsh 2022), but they also differ in their level of cotranslational assembly, with members of the cyclic group being the least likely to cotranslationally assemble ( Figure S1E ). When we subset AD and AR homomers based upon their symmetry group, we find a relatively large variation in the level of cotranslational assembly ( Figure S1F ).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…We have previously shown that cotranslationally assembling members of the different symmetry groups tend to have larger interfaces (Badonyi and Marsh 2022), but they also differ in their level of cotranslational assembly, with members of the cyclic group being the least likely to cotranslationally assemble ( Figure S1E ). When we subset AD and AR homomers based upon their symmetry group, we find a relatively large variation in the level of cotranslational assembly ( Figure S1F ).…”
Section: Resultsmentioning
confidence: 96%
“…The third structural property we investigated is the relative interface location (Badonyi and Marsh 2022). N-terminal regions of proteins are more likely to be involved in cotranslational interactions because of vectorial synthesis on the ribosome, an intuitive assumption supported by experimental observations (Bertolini et al 2021; Kamenova et al 2019; Natan et al 2018; Shiber et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations